The Role of the Language Courses Department in Supporting Listening Readiness among Novice Arabic Learners in a Pesantren - Ahmad Farhan Rif'an Najib; Faqih Nur Fahmi; Yoke Suryadarma; Zidane Taqiyyurrahman; Ikhwan Achmadi; Khansa Nabila (Journal of Arabic Language Learning and Teaching (JALLT), 2026)
This study aims to examine the role of the Language Courses Department (LCD) as a supporting institution in the development of listening readiness among novice Arabic learners in a pesantren context. Although Pondok Modern Darussalam Gontor provides an intensive Arabic-speaking environment, many new students still struggle to comprehend spoken Arabic, indicating that exposure alone is insufficient. This condition underscores the need for institutional support that fosters learners’ psychological, cognitive, and behavioral readiness for listening. Using a qualitative descriptive approach, data were collected through observations, semi-structured interviews, and documentation involving LCD administrators, tutors, and novice learners. Data analysis followed Miles and Huberman’s interactive model. The findings show that LCD performs a multidimensional role as mentor, mediator, motivator, and inspirator through structured listening activities, graded audio-visual materials, interactive practice, and emotional-academic support. These efforts reduce listening anxiety, enhance familiarity with spoken Arabic, improve attentional focus, and encourage responsive learner behavior. Rather than yielding immediate achievement gains, LCD programs function as preparatory support that strengthens listening readiness as a foundation for effective language immersion and formal instruction.